Born Dead or Alive? Revisiting the Definition of Stillbirths in Norway - Sommerseth, Hilde Leikny (Historical Life Course Studies, 2021)
Since 1947 there has been a common understanding among Norwegian historians and demographers that stillbirths registered in the country prior to 1839 included infants who were born alive but died within 24 hours. This paper shows that a revision of this definition is necessary. During the first half of the 19th century, several memoranda, revisions and circulars were distributed by the Danish-Norwegian authorities — and Norwegian authorities after 1814 —, with the purpose of collecting and then improving the registration of stillbirths. After a close reading of these documents, I find no indication that the ’24 hours of life’ limit was explicitly included in the definition of stillbirths at any time prior to 1839. Instead, ’first day deaths’ were given a separate column in the registration forms returned by the priests, midwives and district medical officers who recorded vital events. However, the design of these forms was inconsistent between 1806 and 1831.